Nutritious orange-fleshed-sweetpotato for Niassa, Mozambique - Rakotoarisoa, B.; Antonio, C.M.; Maloa, A.M.M. (International Potato Center, 2015)
The key aim of the ‘Nutritious Orange-Fleshed-Sweetpotato for Niassa, Mozambique' project, which began in November 2012, is to improve vitamin A and energy intake for at least 20,000 rural households with women and young children using orange-fleshed sweetpotato focused, food-based approaches that ensure at least 20% of households growing OFSP earn 50 USD or more per year from OFSP sales, and increase average sweetpotato yields by 50% by mid-2016. It is implemented in 8 districts of Niassa province. This flyer sums up the specific objectives and strategies and achievements of the project from June 2014 to July 2015, and the plans for 2015-2016.